[LB.03.11] WOULD DDD, CONTRARY TO THE TOTAL NUMBER OF DRUGS, BE THE BEST TOOL TO EVALUATE THE EFFECTIVENESS OF ANTIHYPERTENSIVE THERAPY?. (September 2017) - Brunelli, V.; De Faria, A.P.; Cruz, L.A.; Corrêa, N. Batista; Sabbatini, A. Rodrigues; Modolo, R.; Moreno, H.; Ritter, A.M.
Abstract : Objective: This study evaluated the DDD of the prescribed antihypertensive drugs in relation to the number of drugs as well as the blood pressure levels of hypertensive patients during a mean of 5 years follow-up period. Design and method: A retrospective cohort study was carried out to evaluate the medical records of 120 resistant and mild hypertensive patients with a 5-year follow-up in a specialized outpatient clinic (1999–2016). The antihypertensive medication prescribed at the first and the last visit, as well as the pressure parameters were analyzed. STATISTICS: Paired Student t test comparing the continuous variables of the first and last appointment was used. A multiple linear regression model adjusted for age, sex, race and BMI was used to evaluate the association of 1) DDD of antihypertensive drugs and 2) number of antihypertensive drugs prescribed with outpatient pressure variation over the analyzed years. The level of statistical significance was set at 0.05. Results: DDD and the total number of prescribed antihypertensive drugs increased during the follow-up period (4 ± 3 vs. 5 ± 3, p = 0.02, 3 ± 1 vs. 4 ± 1, p < 0.01, respectively). There was a reduction in office blood pressure values (135/79 vs. 140/87 mmHg, p < 0.01) during the analyzed period. Mean 24 hour ambulatory pressure (77 ± 15 vs. 72 ± 15 mmHg, p = 0.03), daytime (80 ± 13 vs. 76 ± 11 mmHg) and nighttime (72 ± 12 vs .69 ± 12 mmHg p < 0.01) also decreased over time. The multiple regression analysis indicated that the DDD of the total number of antihypertensive drugs prescribed was associated with mean ambulatory diastolic BP reduction (β = −1.24; SE = 0.65; p = 0.04). On the other hand, the total number of antihypertensive drugs used was not able to predict this pressure reduction. Conclusions: Although the total number of drugs is indicated as one of the main tools for therapeutic follow-up, our study suggests the use of DDD as an alternative able to predict therapeutic efficacy in hypertensive patients.